2010
DOI: 10.4067/s0718-19572010000300008
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de diferentes niveles de proteína y lípidos totales en la dieta sobre el crecimiento y supervivencia de juveniles de pargo lunarejo Lutjanus guttatus

Abstract: Abstract.-The spotted rose snapper (Lutjanus guttatus) is one of the most commercially important fish species inMéxico. As it is considered a suitable candidate for culture, then it is necessary to identify its nutritional requirements in order to succeed. The aim of this study was to evaluate the effects of different protein and lipid levels on growth and survival of juvenile spotted rose snappers. Nine semi-purified diets were formulated with three protein levels (40, 45 and 50%) and three lipid levels (9, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 17 publications
0
5
0
4
Order By: Relevance
“…guttatus requires protein and lipid values ranging from 45 to 50% and 9 to 15%, respectively, and its diet is mainly based on fish meal as the dietary protein source (Abdo de la Parra et al, 2010a). The limited fish meal supply, coupled with the increasing demand for fish meal, has greatly inflated the cost of this commodity (Tacon & Metian, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…guttatus requires protein and lipid values ranging from 45 to 50% and 9 to 15%, respectively, and its diet is mainly based on fish meal as the dietary protein source (Abdo de la Parra et al, 2010a). The limited fish meal supply, coupled with the increasing demand for fish meal, has greatly inflated the cost of this commodity (Tacon & Metian, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the proximate analysis of the test feed used by the fishermen during the fattening stage showed that the average concentration of lipids was 20.4%; this could be the main trigger of HE. The average protein concentration in these samples was 30.2%, which would classify it as low-protein diet, compared with other studies in which the concentration of proteins required by the diet is higher than 50% (García-Ortega, 2009;Abdo de la Parra et al, 2010). Although the studies conducted on fish do not mention it, in domestic animals the lack of protein is considered a crucial factor for the development of hepatocellular Figure 1.…”
mentioning
confidence: 78%
“…Since lipid metabolism is mainly regulated by the liver, including the synthesis and degradation of fatty acids, an unbalanced diet could affect the structure and function of the liver (Roberts & Ellis, 2012); thus, providing an adequate diet to marine fish is especially important (García-Ortega, 2009;Abdo de la Parra et al, 2010).…”
mentioning
confidence: 99%
“…Se ha demostrado que los peces marinos carnívoros requieren altos niveles proteicos (40-60%) y lipídicos (6-15%) para lograr un óptimo crecimiento (De la Parra et al, 2010). Al respecto, A. scapularis, es una especie marina y carnívora (Medina et al, 2004) que requiere un régimen proteico elevado.…”
Section: Discusión Crecimiento E íNdices De Condiciónunclassified
“…Se ha afirmado que la cantidad de alimento consumido depende de la proporción de proteína y energía de la dieta, indicando que a una mayor concentración de energía reduce la ingestión del alimento y viceversa (Poniak et al, 2004;Escobar et al, 2006;De la Parra et al, 2010). Sin embargo, también se ha postulado que para un organismo el flujo de asimilación se realiza a través de una superficie; por lo tanto, la tasa de ingestión sería una función potencial de la longitud al cuadrado (Kooijman, 2009).…”
Section: íNdices De Alimentaciónunclassified